Understanding and study perspectives on tectonic evolution and crustal structure of the Paleozoic Chinese Tianshan - Wang, Q.; Shu, L.; Charvet, J.; Faure, M.; Ma, H.; Natal'in, B.; Gao, J.; Kroner, A.; Xiao, W.; Li, J.; Windley, B.; Chen, Y.; et al. (International Union of Geological Sciences, 2010)
The Chinese Tianshan Belt is one of the key regions for the understanding of tectonics of the Central Asian Orogenic Belt (CAOB). An international field excursion and workshop were organized to conduct a common observation and discussion on the tectonic evolution of the Chinese Tianshan. This report summarizes the main achievements, including acknowledged geological features, controversial and remaining scientific problems, and discussion of a tentative geodynamic model. Thus, it is helpful to clarify what has been done in the past, what should be improved and what needs to be done in the future and therefore to better understand the tectonics of the Chinese Tianshan Belt and the CAOB as well.